Da interferência da língua materna no ensino de uma língua estrangeira - Lyra, Larissa Raquel Pereira (2013)
Due to the increasing concern of English school teachers about the constant use of the Portuguese language during the "English as a Foreign Language" (EFL) classes, we do believe that a study on the interference of the mother tongue (MT) in the process of a foreign language (FL) acquisition may contribute to the reflections on the relation between the speaker and their languages. To do so, we have adopted contributions of Saussure on the conception of language as a system which knows its own laws. This conception has helped us understand its operation. We have found in Melman, Revuz and Pereira de Castro the notion of the singular character of a mother tongue for the subject, as the language which has founded them as such. In Revuz we have found the issue of the specific bound which gathers the speaker to their Mother Tongue as an important factor for success or failure to acquire a foreign language. Based on Heller-Roazen and Coracini, we will study the the echo of the mother tongue, the mix of languages and the relation between those speakers among languages with their native and foreign languages, and with their respective cultures. This dissertation had the main aim to study the incidence of the mother tongue in the acquisition of a foreign language. To achieve that, we have analysed the different relations which can be established between the subject and their native and foreign languages, and the interference of those relations in the process of acquisition of a foreign language. The participants of this research were non-native adult learners who were in their native country. One group was in an early stage of learning, the Starter 2 group, and the other was in a more advanced stage (conversation course), the Advanced 4 Light group. Right after the classes observation, which happened in the classroom and/or through videos, we analysed the interlocution among the students and between them and the teacher. The results indicate not only that the presence of the mother tongue in both levels is latent, but also that it occupies a place of great value in the relation between the speakers and their foreign language. Regarding the moments in which language switching occurred, the results indicate that, although the Starter 2 students leant on their own language more frequently, we could also observed a strong presence of the Portuguese language in the Advanced 4 Light classes. In both levels we have seen students using Portuguese explicitly and audibly, both in entire statements and when speakers inserted small items of the Portuguese language in statements which were proffered almost completely in English. We have also realised the influence of the speakers mother tongue both in the production of sounds which are typically of English and in the errors, lapses and displacement in statements. We propose the acceptance of the immutable presence of learners mother tongue in the process of a foreign language acquisition, yet the appreciation of such presence in the classroom.